Following the transfer of DNA: How does the presence of background DNA affect the transfer and detection of a target source of DNA?. (November 2015) - Lehmann, VJ; Mitchell, RJ; Ballantyne, KN; Oorschot, RAH van
Highlights: DNA can be transferred from one surface to another several times. Much transfer DNA is transferred during initial contact after deposit. Detection of transferred DNA is dependent on contacting substrates and samples. Detection of transferred DNA lessens when background DNA is from multiple sources. Abstract: DNA transfer is of increasing importance in crime scene situations, partly due to analytical techniques detecting profiles in ever declining amounts of DNA. Whereas the focus has previously been DNA transfer of target sources, the effects of background DNA on transfer and detection of DNA after multiple contact situations have been much less investigated. This study measured the transfer and detection rates of a specific DNA source in the presence of background DNA sources. The presence of background DNA influenced the transfer of DNA differently depending on the combination of biological material and surface type. The detection of a profile from the target DNA decreased after multiple contact situations, due to the reduced total and relative quantity of target DNA, and the increasing complexity of the mixture. The results of this study contribute to a greater understanding of the effects of background DNA sources on DNA transfer and detection.